Hyberbaric oxygen increases atresia in normal & steroid induced PCO rat ovaries - Atis Alev; Aydin Yavuz; Ciftci Filiz; Sakız Damlanur; Arslan Abdullah; Toklu Akın S; Donmez Melahat; Goker Nimet (BMC, 2012)
Abstract Background In this study, we investigated the effect of hyperbaric oxygen therapy (HBOT) on the morphology of estradiol valerate (EV) induced polycystic ovary (PCO) to find a new treatment modality for improvement of PCO. Methods The rats were divided into four groups. Group1, control; group 2, PCO group; group 3, PCO with HBOT group and group 4, normal ovary with HBOT. PCO was induced by a single intramuscular injection of 4 mg EV in adult cycling rats. Other rats with normal ovaries had oil injection as placebo. HBOT was applied to third and fourth groups for six weeks. Histopathologic evaluation of ovaries of all groups were performed & compared. Results Six weeks of HBOT was resulted in increase in follicular atresia, decrease in the number of primary, secondary, tertiary follicles and decrease in the number of fresh corpus luteum in normal rat ovary. HBOT on polycystic rat ovary, resulted in significant increase in atretic follicles which were already present. Conclusions HBOT of six weeks itself, changed ovarian morphology in favor of atresia both in PCO group and control group. This result of aggravated follicular atresia after HBOT on EV induced PCO may be due to long-term exposure in our protocol which with this state seems to be inapplicable in the improvement of PCO morphology.